Peranan dan Kedudukan Hukum Lingkungan Internasional Dewasa Ini - Silalahi, Daud (Indonesian Journal of International Law, 2005)
Since the Stockholm Declaraton of 1972, the principles of environmental legal principles fundamentally changed the formulation of new international environmental law. The formuation of environmental legal provision was significantly influenced by a scientific approach, such as ecological and environmental concepts. The role of international environmental law is increasingly greater on the ecological approach rather than on the general principles of international law. The structure of international environmental law is also changed related to, among others, state responsibility, states rights and obligations, and the rising of the eco-rights and the animal rights that fundamentally changed the customary international law approach into new progressive development of international environmental law. Through ratification, the national environmental law has been significantly improved, and there is a growing recognition of the integrated system of national environmental law and international environmental law.